Injury risk potential and flexibility level: An analysis of amateur team sport athletes - Herstiani-S, Alfina; Anam, Khoiril (Journal Sport Area, 2024)
Background Problems: Sports injuries are a severe problem that can affect an athlete's career, including those active in team sports such as basketball, volleyball, and futsal. Research Objectives: This study aims to analyse the potential risk of injury and the level of flexibility of amateur athletes at Universitas Negeri Semarang. Methods: This research is a quantitative descriptive study using the sampling technique, namely purposive sampling, to obtain a total sample of 90 athletes. Instruments to measure the potential risk of injury use the functional movement screen (FMS) and the level of flexibility using the sit-and-reach test. The data analysis techniques use descriptive statistical analysis. Findings and Results: The results of the FMS analysis showed that most male and female amateur athletes had a low level of injury risk. Flexibility measurements show that most male and female amateur athletes have good flexibility. This study contributes to understanding the potential risk of injury and the level of flexibility in amateur team sport athletes. Conclusion: The findings can assist coaches and teams in designing more effective training programmes to improve athletes' physical health and performance. Further research is recommended to analyse other physical condition component variables, as well as research subjects from different age groups. In addition, it is also recommended that more research samples from various levels of athletes be examined.